PAEDIATRICIANS: ARE THEY JUST LITTLE ADULTS?. Issue 12 (18th November 2016) - Tabner, A; Johnson, G; Jones, M; Patel, R; Husk, K; Parish, R; Rees, J; Henstridge, V; Clark, I; Thomas, V; Hearnshaw, C
Abstract : Objectives & Background: Being well acquainted with the oft-repeated premise that "children are not little adults", we set out to test the hypothesis that paediatricians are little adults. Methods: Design International cross-sectional study. Setting Six hospitals (both academic and non-academic centres) in the United Kingdom and New Zealand. Participants Sample of 61 paediatricians, 57 emergency medicine physicians, 31 general internal medicine physicians and 15 healthcare of the older person physicians were recruited; there were no losses to follow-up. All potentially eligible participants (doctors with >2 years experience in one of the above specialties) at the study sites were invited to take part; all willing participants were recruited. Specialties excluded were surgery, anaesthetics, intensive care (and the paediatric versions thereof) as well as specialties such as microbiology and pathology that have little patient-facing contact. Main outcome measures Height (cm), weight (kg), BMI, head circumference (cm), shoe size (UK system), gender, speciality, age, years in speciality, whole time equivalence, institution, country of birth, country of practise. Results: Paediatricians were significantly shorter than non-paediatricians (mean height 168.0 v 173.9 cm; mean difference 5.9 cm; 95% confidence interval 2.8 to 9.1; p<0.001). This difference was maintained when adjusted for participant gender and country of birth (5.0; 2.3 to 7.8; p<0.001). Paediatricians were also lighter than non-paediatricians (mean weight 70.0 v 78.0 kg; mean difference 8.0 kg; 3.0 to 13.1; P=0.02) and wore smaller shoes (mean size 6.8 v 8.0 UK; mean difference 1.2 UK; 0.5 to 1.9; P=0.0001). Both of these differences also persisted when adjusted for participant gender and country of birth. There was no significant difference in the head circumference or Body Mass Index between paediatricians and non-paediatricians. ROC analysis suggests that paediatric speciality may be 'diagnosed' at a height of 159.00 cm with specificity 92.2% and sensitivity 16.4%. Conclusion: This study provides the first evidence that paediatricians are physically smaller doctors. The startling implications for targeted recruitment have been discussed.Figure 1 Figure 2 Figure 3 Table 1 Table 2